2005
DOI: 10.1038/sj.cgt.7700840
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient killing of quiescent human epithelial cells by replicating adenoviruses: potential implications for their use as oncolytic agents

Abstract: Cultured primary human cells have been widely used to assess the selectivity of oncolytic viruses as potential anticancer agents. As culture conditions can potentially have a significant impact on virus replication and ultimately cell killing, we evaluated the effects of dl309, a wild-type adenovirus, and dl01/07, a conditionally replicating adenovirus mutant, on quiescent and proliferating primary mammary epithelial cells. When primary cells were induced into quiescence, both viruses exhibited similar attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
1
13
0
2
Order By: Relevance
“…6A), S + G 2 -M cycling cells constituted 81% of dl309-treated cells, 73% of Internavec-treated cells, and 58% of ONYX-411-treated cells at 96 hours post-infection. These findings were consistent with previous reports (28,29) of E1A and E4 early adenoviral genes overriding the fundamental control of the host cell cycle, forcing progression into the cell cycle. Furthermore, Internavec treatment, but not ONYX-411, produced significantly elevated accumulation of cells in S + G 2 -M phases as compared with untreated cultures at 72 hours (68 F 8.4% versus 52 F 0.4%, n = 3; P = 0.028) and 96 hours (71 F 7.2% versus 49 F 3.8%, n = 3; P = 0.01; mean F SD).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…6A), S + G 2 -M cycling cells constituted 81% of dl309-treated cells, 73% of Internavec-treated cells, and 58% of ONYX-411-treated cells at 96 hours post-infection. These findings were consistent with previous reports (28,29) of E1A and E4 early adenoviral genes overriding the fundamental control of the host cell cycle, forcing progression into the cell cycle. Furthermore, Internavec treatment, but not ONYX-411, produced significantly elevated accumulation of cells in S + G 2 -M phases as compared with untreated cultures at 72 hours (68 F 8.4% versus 52 F 0.4%, n = 3; P = 0.028) and 96 hours (71 F 7.2% versus 49 F 3.8%, n = 3; P = 0.01; mean F SD).…”
Section: Resultssupporting
confidence: 83%
“…The self-limiting disease course of wild-type adenoviral infections in immunocompromised patients is indicative of limited virulence (29). Host cells with viral protein expression are commonly seen post-infection, indicative of an aborted viral replicative process and/or a latent infection state (13,28,29). Coupled with the common defects in apoptotic and IFN-induction pathways in cancer cells, the aborted oncolytic process is an explanation for incomplete clinical responses seen in oncolytic virotherapy trials (14,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We preselected the virus Ad5/3 as optimal for our strategy by screening a virus panel and picking a virus with limited cytopathic effect in MPCs and maximum cytopathic effect in the tumor cell line. It has been shown that wild-type adenoviral replicates and kills highly proliferating cells more efficiently and therefore only exerts an attenuated effect on quiescent cells (48). This could explain the lower cytopathic effect rate of adenoviruses on MPCs compared with tumor cells.…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, wild-type adenoviral infections of even immunocompromised patients often produced self-limiting disease, which is indicative of the limited virulence of the adenovirus [Vaillancourt et al, 2005;Hogg, 2001]. The expression of viral proteins by the host cell without replication of a complete virus has been well documented in adenovirus-infected host tissues [Elliott et al, 1995;Rao et al, 2004].…”
Section: Oncolytic Viral Delivery Of Transgenes With Oncogene Knockdomentioning
confidence: 99%